Investigation of Antibiotic-Resistant Enterobacteriaceae Isolated from Soaked Sheepskins and Cattle Hides - (:unkn) unknown (SOC LEATHER TECHNOL CHEMISTS, 2019)
Antimicrobial resistance of bacteria in human and veterinary medicine has been examined for many years, but there is no information about antimicrobial resistance of Enterobacteriaceae isolated from soaked sheepskins and cattle hides. Therefore the antibiotic resistance of Enterobacteriaceae isolated from soaked sheepskins and cattle hides was investigated. The antibiotic resistance of soaked skin isolates (Citrobacter freundii, Citrobacter koseri, Cronobacter sakazakii, Enterobacter amnigenus, Enterobacter cloacae, Morganella morganii, Proteus mirabilis, Providencia rettgeri) and soaked hide isolates (Citrobacter koseri, Cronobacter sakazakii, Morganella morganii, Providencia rettgeri, Serratia marcescens, Serratia plymuthica, Serratia rubidae) towards 24 different antibiotics were examined using the disc diffusion method. Among thirteen skin isolates, the percentages of resistance against antibiotics used were aztreonam 92%, ampicillin 69%, ceftriaxone 69%, streptomycin 62%, cephalothin 62%, amoxicillin/clavulanate 62%, ceftazidime 61%, nalidixic acid 54%, ciprofloxacin 54%, chloramphenicol 46%, piperacillin/tazobactam 46%, cefuroxime sodium 46%, tetracycline 31%, sulfamethoxazole-trimethoprim 15%, cefoxitin 15%, ampicillin/sulbactam 15%, kanamycin 15%, tobramycin 8%, meropenem 8% and imipenem 8%. Among ten hide isolates, the percentages of resistance against antibiotics were, ampicillin 80%, amoxicillin/clavulanate 80%, tetracycline 70%, cefuroxime sodium 70%, streptomycin 60%, aztreonam 50%, ceftriaxone 40%, chloramphenicol 30%, ceftazidime 20%, cephalothin 20%, nalidixic acid 30%, cefoxitin 20%, ampicillin/sulbactam 20%, piperacillin/tazobactam 20%, ciprofloxacin 20% and kanamycin 10%. While all skin isolates were susceptible to amikacin, gentamicin, ofloxacin, and norfloxacin, all hide isolates were susceptible to amikacin, gentamicin, tobramycin, meropenem, sulfamethoxazole-trimethoprim, norfloxacin and ofloxacin. As a conclusion, the species of the family Enterobacteriaceae which were resistant to the antibiotics used in human and veterinary medicine were detected on the soaked skins and hides in the leather industry.
Keywords: PENICILLIN; BACTERIA